Thrombotic Markers in Pregnant Patients with and without SARS-CoV-2 Infection - Bruno, Ann M.; Allshouse, Amanda A.; Benson, Ashley E.; Yost, Christian Con; Metz, Torri D.; Varner, Michael W.; Silver, Robert M.; Branch, D. Ware (American Journal of Perinatology, 2023)
Background Coronavirus disease 2019 (COVID-19) is associated with coagulation abnormalities and increased risk for venous and arterial thrombi. This study aimed to evaluate D-dimer levels and lupus anticoagulant (LAC) positivity in pregnant individuals with and without Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.Study Design This was a prospective cohort study of pregnant individuals delivering at a single academic institution from April 2020 to March 2022. Individuals with a positive SARS-CoV-2 result during pregnancy were compared with a convenience sample of those without a positive SARS-CoV-2 result. For individuals with SARS-CoV-2 infection, severity was assessed based on the National Institutes of Health classification system. The primary outcome was D-dimer level measured during delivery admission. The secondary outcomes were LAC positivity and thromboembolic events. Outcomes were compared between individuals with and without a positive SARS-CoV-2 result, and further by disease severity.Results Of 98 participants, 77 (78.6%) were SARS-CoV-2 positive during pregnancy. Among individuals with SARS-CoV-2 infection, severity was asymptomatic in 20 (26.0%), mild in 13 (16.9%), moderate in 4 (5.2%), severe in 38 (49.4%), and critical in 2 (2.6%). The D-dimer concentration at delivery did not significantly differ between those with a SARS-CoV-2 positive result compared with those without (mean 2.03 µg/mL [95% confidence interval CI 1.72–2.40] vs. 2.37 µg/mL [95% CI 1.65–3.40]; p = 0.43). Three individuals (4%) with SARS-CoV-2 infection and none (0%) without infection were LAC positive (p = 0.59). There were no clinically apparent thromboses in either group. D-dimer concentrations and LAC positive results did not differ by COVID-19 severity.Conclusion Thrombotic markers did not differ in pregnant individuals by SARS-CoV-2 infection; however, high rates of LAC positivity were detected.Key Points
Keywords: thromboembolism; thrombotic biomarkers; SARS-CoV-2 infection; lupus anticoagulant; D-dimer